The panchromatic hubble andromeda treasury . VIII. A wide-area, high-resolution map of dust extinction in M31 - Dalcanton, Julianne J.; Fouesneau, Morgan; Hogg, David W.; Lang, Dustin; Leroy, Adam K.; Gordon, Karl D.; Sandstrom, Karin; Weisz, Daniel R.; Williams, Benjamin F.; Bell, Eric F.; Dong, Hui; Gilbert, Karoline M.; et al. (The astrophysical journal, 2015)
We map the distribution of dust in M31 at 25 pc resolution using stellar photometry from the Panchromatic Hubble Andromeda Treasury survey. The map is derived with a new technique that models the near-infrared color-magnitude diagram (CMD) of red giant branch (RGB) stars. The model CMDs combine an unreddened foreground of RGB stars with a reddened background population viewed through a log-normal column density distribution of dust. Fits to the model constrain the median extinction, the width of the extinction distribution, and the fraction of reddened stars in each 25 pc cell. The resulting extinction map has a factor of ≳4 times better resolution than maps of dust emission, while providing a more direct measurement of the dust column. There is superb morphological agreement between the new map and maps of the extinction inferred from dust emission by Draine et al. However, the widely used Draine & Li dust models overpredict the observed extinction by a factor of ∼2.5, suggesting that M31's true dust mass is lower and that dust grains are significantly more emissive than assumed in Draine et al. The observed factor of ∼2.5 discrepancy is consistent with similar findings in the Milky Way by the Plank Collaboration et al., but we find a more complex dependence on parameters from the Draine & Li dust models. We also show that the the discrepancy with the Draine et al. map is lowest where the current interstellar radiation field has a harder spectrum than average. We discuss possible improvements to the CMD dust mapping technique, and explore further applications in both M31 and other galaxies.
Gesehen am 16.12.2020